The Effect of Two Combinations of Direct Fed Microbials on Growth Performance of Nursery Pigs Weaned from Sows Fed Diets with or without Yeast Additives - Jenna A. Chance; Jordan T. Gebhardt; Joel M DeRouchey; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joseph A. Loughmiller (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 330 weaned pigs (Line 241 × 600, DNA; initially 12.7 lb BW) were used in a 38-d nursery study to evaluate previous sow treatment (control vs. yeast additives) and nursery diets with different combinations of direct fed microbials (DFMs; Phileo by Lesaffre, Milwaukee, WI) on nursery pig growth performance. Pigs were placed in pens across two nursery rooms at weaning then pens were assigned to 1 of 3 dietary treatments with 6 pigs per pen and 8 to 10 replications per treatment. Treatments were arranged in a 2 × 3 factorial with main effects of sow treatment (control vs. yeast additives; 0.10% ActiSaf Sc 47 HR+ and 0.025% SafMannan) and nursery treatment (control; DFM 1, 0.05% of SafMannan from d 0 to 38 and NucleoSaf at 0.05% from d 0 to 10 and 0.025% from d 10 to 24; or DFM 2, 0.10% MicroSaf from d 0 to 38 and NucleoSaf at 0.05% from d 0 to 10 and 0.025% from d 10 to 24). Data were analyzed using linear mixed models using the nlme package of R with fixed effects of sow treatment, nursery treatment, and their interaction, and nursery room serving as the random effect. During the first ten days post-weaning, progeny of sows fed yeast additives had improved (P<0.05) ADG, ADFI, and G:F. In fact, while pigs weaned from sows fed yeast additives entered the nursery at a lighter (P<0.001) BW compared to pigs weaned from sows fed the control diet, by d 10 there was no difference (P>0.10) in BW between the two groups. Offspring from sows fed yeast additives tended to have improved (P = 0.069) overall F/G. Pigs fed DFM 2 had increased (P<0.05) ADG from d 24 to 38, and improved end of nursery BW compared to pigs fed the control diet. In conclusion, feeding yeast additives to sows had a positive impact on progeny growth in the early nursery, while the addition of DFMs in nursery diets had more impact on growth later in the nursery period.
Keywords: lactation; nursery pigs; probiotics; live yeast; yeast extracts